Iterative method for clearances and insulation levels based on switching surge - T. Thanasaksiri (2018)
© 2015 IEEE. This paper analyzes the insulation levels and clearances of 230 kV air insulated substation based on switching surge. The basic switching impulse insulation levels (BSL) and air clearances, both for phase to ground and phase to phase have been calculated. In order to get the insulation levels, BSL and clearances, the iterative method is required. The insulation levels and clearances have been implemented applying IEEE Std. 1427. The method for calculating the BSL and clearances have been compared with the procedure given in IEC 60071-2. The effect of elevation from sea level has also been considered for insulation levels and clearances.